Development of integrated optoelectronic system for search and rescue mission control - Sajkowski, Maciej; Stenzel, Tomasz; Boratyński, Tomasz; Bokszczanin, Jan; Kruk, Tomasz (Photonics Letters of Poland, 2016)
In this work, the results of development of optoelectronic system designed for search and rescue maritime operation are presented. Due to integration a number of few data sources in the console of the system operator, the main focus of the paper is signal interfaces and data flow within the developed solution. The structure of the system is described as well as data flow for images and control is presented. Finally, the images showing examples of system operation are shown. Full Text: PDF References G. Bieszczad, T. Sosnowski, H. Madura, M. Kastek, J. Bareła, "Image processing module for high-speed thermal camera with cooled detector", Proc. SPIE 8012, Infrared Technology and Applications XXXVII 80120L (2011). CrossRef N.K. Dhar, R. Dat, A.K. Sood in Optoelectronics - Advanced Materials and Devices, S. Pyshkin (Ed.), InTech (2013). DirectLink O.W. Ibraheem, A. Irwansyah, J. Hagemeyer, M. Porrmann, U. Rueckert, 2015 International Conference on ReConFigurable Computing and FPGAs (ReConFig), 1 (2015). DirectLink K.D. Nibir, D. Ravi, K.S. Ashok in Optoelectronics - Advanced Materials and Devices, S. Pyshkin (Ed.), InTech (2013); available from: http://www.intechopen.com/books/optoelectronics-advanced-materials-and-devices/advances-in-infrared-detector-array-technology DirectLink E. Norouznezhad, A. Bigdeli, A. Postula, B.C. Lovell, "A high resolution smart camera with GigE Vision extension for surveillance applications", ACM/IEEE Second International Conference on Distributed Smart Cameras ICDSC 2008, 1 (2008). CrossRef A. Rogalski, "Progress in focal plane array technologies", Prog. Quantum Electron. 36(2), 342 (2012). CrossRef A. Rogalski, "Infrared Detectors for the Future", Acta Phys. Polonica A 116(3), 389 (2009). CrossRef A. Rogalski, "Semiconductor detectors and focal plane arrays for far-infrared imaging", Opto-Electr. Review 21(4), 406 (2013). CrossRef T. Sprafke, J.W. Beletic, "High-Performance Infrared Focal Plane Arrays for Space Applications", Optics & Photon. News 19, 22 (2008). CrossRef J. Stachiw, D. Endicott, "Material and Design Considerations for Thermal Imager Windows in Marine Service", Oceans ’79, 424 (1979). CrossRef W. Yuan He, K.H. Xiao, Z. Xu, "A high speed robot vision system with GigE vision extension", IEEE International Conference on Mechatronics and Automation, 452 (2011). CrossRef